2020
DOI: 10.1002/ccd.28756
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography‐defined plaque vulnerability in relation to functional stenosis severity stratified by fractional flow reserve and quantitative flow ratio

Abstract: Objectives We sought to investigate that the quantitative flow ratio (QFR) might be associated with optical coherence tomography (OCT)‐defined plaque vulnerability. Background Both functional stenosis severity and plaque instability are related to adverse clinical outcomes in patients with coronary artery disease. Recent studies have shown an association between physiological stenosis severity and the presence of thin‐cap fibroatheroma (TCFA). Measurement of QFR is a novel method for rapid computational estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…However, the majority of the included lesions (89%) were from patients with stable coronary artery disease and this association needs to be verified in a broader spectrum of patients. Additionally, discrepant results were reported in previous studies examining whether plaque characteristics assessed by OCT ( 14 16 ) or VH-IVUS ( 17 20 ) had an impact on coronary hemodynamics. Hence, the association between coronary physiology and OCT/IVUS-defined plaque vulnerability remains elusive and warrants more evidence.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, the majority of the included lesions (89%) were from patients with stable coronary artery disease and this association needs to be verified in a broader spectrum of patients. Additionally, discrepant results were reported in previous studies examining whether plaque characteristics assessed by OCT ( 14 16 ) or VH-IVUS ( 17 20 ) had an impact on coronary hemodynamics. Hence, the association between coronary physiology and OCT/IVUS-defined plaque vulnerability remains elusive and warrants more evidence.…”
Section: Introductionmentioning
confidence: 72%
“…A recent study indicated the link between QFR and the presence of OCT-TCFA in 327 de novo intermediate-to-severe coronary lesions but the majority of these lesions were from stable patients ( 14 ). Here, we further confirmed this relationship in an NSTE-ACS-dominated population and suggested the applicability of QFR in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Kanno et al [ 25 ] showed that a lower QFR may be associated to a higher rate of thin capped fibroatheromas in the investigated lesions. We aimed to extend the current knowledge by further assessing plaque vulnerability, as determined by OCT, in dependence of QFR.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, CMR can also evaluate the extent of ischemia, which yields a relevant value in risk stratification [ 1 , 8 ]. The correlation between the presence of ischemia and geometry of a coronary lesion has already been shown [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]; however, to date, no study evaluated whether stenosis parameters predict also the extent of this ischemia. This may be clinically relevant, especially if there is no previous quantification of the ischemic burden because it may give interventionalists insights into the extent of ischemia based on the geometric features of the coronary lesion and may be a valuable addition to functional testings such as FFR or iFR.…”
Section: Discussionmentioning
confidence: 99%